PENGARUH MODEL PEMBELAJARAN ONLINE TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS NEGERI MAKASAR - MUHAMMAD IQBAL REZKY; THAMRIN TAHIR; MUHAMMAD HASAN; INANNA; MUHAMMAD DINAR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The purpose of this study is to see if the Online Learning Model has an impact on the learning outcomes of economic education students at Makassar State University’s Faculty of Economics. This study is classified as a quantitative descriptive study using a correlation method. A sample of 147 students was taken from the population of 498 active students in the economic education study program for the 2020-2021 academic year. Observation and questionnaire techniques were used to obtain data. Simple linear regression was employed as the analysis strategy. The findings show that Online Learning has a favorable and significant impact on student learning outcomes in the Economics Education Study Program at Makassar State University, either partially or concurrently. With a value of 0.784, online learning has a positive effect on Learning Outcomes, indicating that the variable has a strong association. The coefficient of determination is 0.614, indicating that online learning influences learning outcomes for students in the Economics Education study program by 61.4 percent, with the remaining 38.6 percent influenced by characteristics not included in this study